Bereavement support for family caregivers: The gap between guidelines and practice in palliative care - Aoun, Samar; Rumbold, B.; Howting, Denise; Bolleter, A.; Breen, Lauren (Public Library of Science, 2017)
Background: Standards for bereavement care propose that support should be matched to risk and need. However, studies in many countries demonstrate that palliative care services continue to adopt a generic approach in offering support to bereaved families. Objective: To identify patterns of bereavement support in palliative care services based upon the experience of bereaved people from a population based survey and in relation to clinical practice guidelines. Design: An anonymous postal survey collected information from clients of six funeral providers in four Australian states (2014–15), 6 to 24 months after the death of their family member or friend, with 1,139 responding. Responses from 506 bereaved relatives of people who had terminal illnesses were analysed. Of these, 298 had used palliative care services and 208 had not. Results: More people with cancer (64%) had received palliative care in comparison to other illnesses such as heart disease, dementia and organ failure (4–10%). The support for family caregivers before and after their relative’s death was not considered optimal. Only 39.4% of the bereaved reported bei ng specifically asked about their emotional/ psychological distress pre-bereavement, and just half of the bereaved perceived they had enough support from palliative care services. Half of the bereaved had a follow up contact from the service at 3–6 weeks, and a quarter had a follow-up at 6 months. Their qualitative feedback underlined the limited helpfulness of the blanket approach to bereavement support, which was often described as “not personal” or “generic”, or “just standard practice”. Conclusions: Timeliness and consistency of relationship is crucial to building rapport and trust in the service’s ability to help at post-bereavement as well as a focus on the specific rather than the generic needs of the bereaved. In light of these limitations, palliative care services might do better investing their efforts principally in assessing and supporting family caregivers during the pre-bereavement period and developing community capacity and referral pathways for bereavement care. Our findings suggest that bereavement support in Australian palliative care services has only a tenuous relationship with guidelines and assessment tools, a conclusion also drawn in studies from other countries, emphasizing the international implications of our study. © 2017 Aoun et al.